Efektivitas Sistem Penggajian ASN, Implikasinya terhadap Kompensasi Gaji pada Satpol PP Kota Palembang - Feri Santoro; Siti Nurhayati Nafsiah (CV. ALIM'SPUBLISHING, 2026)
This study aims to analyze the effectiveness of the Civil Apparatus (ASN) payroll system and its implications for salary compensation at the Palembang City Civil Service Police Unit (Satpol PP). The study employed a descriptive method with a qualitative approach. Data were collected through observation, interviews, documentation, and literature review conducted from March to June 2026. The findings indicate that the ASN payroll system has been implemented effectively, as reflected in the timeliness and accuracy of salary payments, accurate employee data management, system transparency, simple administrative procedures, employee satisfaction, and the system’s ability to minimize administrative errors. The effective payroll system positively affects salary compensation by improving employee welfare, increasing work motivation, strengthening discipline, and enhancing organizational productivity. However, several technical and administrative challenges remain, including delays in updating employee data, inconsistencies in attendance records, data input errors, and occasional information system disruptions. These constraints have not significantly affected the salary payment process and remain manageable. Therefore, this study recommends optimizing the payroll information system, improving employee data accuracy, strengthening internal control mechanisms, enhancing the competence of payroll management personnel, and increasing coordination among work units to further improve the effectiveness and reliability of the ASN payroll system.